The effects of environmental patents on renewable energy consumption - Mihaela Onofrei; Bogdan Narcis Fîrțescu; Florin Oprea; Dana Claudia Cojocaru (Green Finance)
Environmental degradation and energy security are two of policymakers' most crucial concerns, with an increasing emphasis on renewable energy development. Studies regarding the role and influence of environmental technology patents in this context become necessary and can provide the empirical evidence needed for public policy decisions in terms of the benefits they bring compared to other innovation measures. Thus, our aim was to capture the effects of environmental technology patents on renewable energy consumption in OECD Member States over the period 2000–2021. We applied the general dynamic panel model with heterogeneous slopes and interactive fixed effects, controlling for cross – sectional dependence and long-run error – correction models based on (Pesaran, 2015) and implemented by Ditzen (2018), and Blackburne Ⅲ & Frank (2007), respectively. The empirical results demonstrated that environmental technology patents can be interpreted as effective mediating mechanisms for increasing renewable energy consumption, thus contributing to a reorientation of activities and consumption toward sustainable development. In other words, environmental patents appear in the transformation equation as the main trigger for innovation, generating a growing influence as the demand for the use of renewable energy sources increases, thus facilitating the transition process towards a (cleaner) and affordable energy market. Based on these results, we believe that policymakers and regulators should pay more attention to the research financing related to the investment and patenting of new environmental technologies, promoting a policy of encouraging and enforcing green technologies, regardless of their scope of application.